What Do Students Expect in a High-Quality Respiratory Care Program?...American Association for Respiratory Care (AARC) Congress, November 20-23, 2024, Orlando, Florida. - Wilshire, Raul; Ramirez, Kristina; Sigarrillo, Ana; Tate, Kyla; Wilson, Taylor; Restrepo, Ruben D (Respiratory Care)
Background: There are only few Master of Science in Respiratory Care (MSRC) programs in the U.S. They are designed to prepare competent advanced level RTs. While evaluating perspectives of existing MSRC programs and their infrastructures, most programs rely on survey-based research from current or recently graduated students to determine their quality. Exit surveys are distributed to new grads to identify variables that can be addressed to improve program quality. However, a distinct gap exists in research specifically targeting the quality of respiratory care education, making this study a unique and valuable contribution to the field. The purpose of this study was to determine specific variables that graduates consider important to qualify their educational program. Methods: Exit surveys were distributed to all students who graduated between 2018 and 2022 from the MSRC program at UT Health San Antonio. The survey consisted of 55 items to assess achievement of program competencies, curriculum, faculty, quality of instruction, learning resources, tuition, financial aid, clinical rotations, and career planning. A Likert scale was used to rate each item. Descriptive statistics and Pearson product-moment correlations were performed (Statistica 14.0.1, StatSoft, TIBCO Data Science). IRB approval was obtained. Results: Exit survey data was collected from 186 students who graduated from UT Health MSRC between the years 2018 to 2022. Mean age for participants was 27.6 (± 5.0) y. Most respondents were female (69.4%), attending full-time (99.8%), and Hispanic or Latino (38.8%). Overall satisfaction with the quality of the MSRC educational program was 4.12 (± 0.8) on a 5-point scale. The 5 variables that participants scored the highest on program included provided knowledge (4.56 ± 0.63), provided technical skills (4.49 ± 0.60), prepared me to conduct myself ethically (4.49 ± 0.63), prepared me to think critically (4.47 ± 0.60), and campus safety (4.46 ± 0.59). Topics related to blend and variety (R = 0.91), quality instruction (R = 0.98), faculty (R = 0.95), and mentoring (R = 0.91) demonstrated the highest correlation with the quality of the UTHSCSA MSRC program. Conclusions: The results of this study suggest that the quality of instruction is a critical component to determine how well students will score their MSRC educational program. There are important aspects of education like ethics and critical thinking that probably need more emphasis as students are ready to be part of the task force.